(untitled) (Physical Education, Health and Social Sciences, 2026)
Tizanidine hydrochloride is a centrally act as skeletal muscle relaxant and is used to manage spasticity in neurological disorders such as multiple sclerosis and spinal cord injury. The current study aimed to develop and evaluate controlled-release (CR) matrix tablets of Tizanidine hydrochloride to achieve sustained drug release and improved therapeutic performance. Control Release tablets were prepared using polymers including Hydroxypropyl Methylcellulose (HPMC K100M), Ethylcellulose (Ethocel 10FP), and Kollidon SR in varying concentrations through direct compression. The formulations were evaluated for hardness, friability, weight variation, drug content, and in-vitro dissolution for 12 hours. Release kinetics was analyzed using zero-order, first-order, Higuchi, and Korsmeyer–Peppas models. Results indicated that polymer type and concentration significantly affected drug release, with HPMC-based formulations showing sustained diffusion-controlled release, while Ethocel and Kollidon SR provided slower or balanced profiles. The optimized formulation sustained drug release for up to 12 hours, following near zero-order kinetics. All formulations exhibited acceptable physical and chemical properties. However, further in-vivo studies and long-term stability assessments are required to establish pharmacokinetic correlation and clinical efficacy